Praktik Pemberian Salinan Akta Oleh Notaris Yang Minuta Aktanya Belum Ditanda Tangani Secara Lengkap - Dalfi, Alfin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
In the routine inspection of the Padang Notary Regional Supervisory Council in 2019, according to his authority in Article 70 letter b UUJN 5 (five) findings of violations were found in the routine inspection of the Notary protocol where there was a violation in the form of incomplete signature of the notary deed. The formulation of this research is why in practice there was a giving of a copy of an act by a notary whose minutes of the deed had not been signed entirely and how the legal consequences of granting a copy of the deed by a notary whose minutes of the act had not been approved in full. This research is analytical descriptive research. Notary Deed has perfect proof of strength in a civil lawsuit, but if it violates specific provisions, the value of the evidence will be degraded to the strength of evidence as a deed under the hand. A notary who is proven to have made a mistake resulting in the act he made only has the power of proof as a deed under the side or even the deed is null and void by law, it will cause harm to the parties.